Design of the electronic control system for the data acquisition from a vertical crop of Pleurotus Ostreatus at the CDA Chia - Zambrano Cortés, Nelson Humberto
The following article reflects the processesand results of the work done for the automaticcontrol of a vertical crop of Pleurotus Ostreatus,better known as Orellana, which is an ediblemushroom. This paper presents the state of theart of the research and the design process of thetemperature and humidity data acquisition systemof the developed crop.